Encyclopedia of the Harlem Renaissance - Wintz, Cary D., 1943-; Finkelman, Paul, 1949- (Routledge, 2004)
An interdisciplinary look at the Harlem Renaissance, it includes essays on the principal participants, those who defined the political, intellectual and cultural milieu in which the Renaissance existed; on important events and places.